Composição centesimal, potencial antioxidante e perfil dos ácidos graxos de sementes de jambolão (Syzygium cumini L.) - Luzia, Débora Maria Moreno [UNESP]; Jorge, Neuza [UNESP] (My University, 2009)
The aim of this work was to characterize jambolan seeds regarding its centesimal composition, and also to evaluate its antioxidant potential and fatty acid profile. To obtain the extract, dehydrated and grinded seeds were extracted with ethyl alcohol for 30 minutes, at a proportion of 1:3 of seeds:ethyl alcohol, under continuous agitation, at room temperature. Afterwards, the mixture was filtered and the supernatant subjected to a rotoevaporator at 40 °C aiming to determine, by direct weighing, the extract's dry matter yield. According to the results of centesimal composition, higher values were found for total carbohydrates. Ethanolic extract from jambolan seeds exhibited antioxidant potential, given by the EC50 value, as well as by the amount of total phenolic compounds. In the oil studied, higher percentage of unsatured fatty acids stood out, being linoleic acid the main component, considered an essential fatty acid.
Analytical composition, antioxidant potential and fatty acid profile of jambolan (Syzygium cumini L.) seeds
Keywords: Gas chromatography; Jambolan seeds; Phenolic compounds